2010
DOI: 10.1186/1472-6750-10-77
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal vaccination with messenger RNA as a new approach in gene therapy: Use against tuberculosis

Abstract: BackgroundmRNAs are highly versatile, non-toxic molecules that are easy to produce and store, which can allow transient protein expression in all cell types. The safety aspects of mRNA-based treatments in gene therapy make this molecule one of the most promising active components of therapeutic or prophylactic methods. The use of mRNA as strategy for the stimulation of the immune system has been used mainly in current strategies for the cancer treatment but until now no one tested this molecule as vaccine for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 40 publications
1
46
0
1
Order By: Relevance
“…The reason for this could be that the robust innate immune response mediated by cholera toxin facilitated the induction of an adaptive immune response following naked mRNA immunization in the nasal cavity. This corroborates data from another study demonstrating that nasally administered naked mRNA induces immune responses for the treatment of tuberculosis26.…”
Section: Discussionsupporting
confidence: 90%
“…The reason for this could be that the robust innate immune response mediated by cholera toxin facilitated the induction of an adaptive immune response following naked mRNA immunization in the nasal cavity. This corroborates data from another study demonstrating that nasally administered naked mRNA induces immune responses for the treatment of tuberculosis26.…”
Section: Discussionsupporting
confidence: 90%
“…In a separate study, Kasturi and colleagues showed that purified HA alone did not elicit virusneutralizing antibody titers, whereas the addition of a TLR7 ligand to HA increased antibody production in mice (30). The additions of synthetic TLR7 agonist to subunit-, purified protein-, or mRNA-based vaccines were shown to enhance the immunogenicity of vaccines against a variety of targets (17,29,39,53,62). Collectively, these studies show that the presence of vRNA that engages TLR7 signaling contributes to the immunogenicity of commercially available TIVs.…”
Section: Fig 3 Tlr7mentioning
confidence: 99%
“…In general, RNA vaccines exhibit a similar spectrum of applications and similar dose effectiveness as DNA vaccines (Carralot et al, 2004;Pascolo, 2004). RNA vaccines are usually prepared by in vitro transcription of mRNA from linearized plasmid DNA containing a bacteriophage promoter (T7, SP6, or T3) followed by poly A extension (Lorenzi et al, 2010). RNA vaccines can also be derived from subgenomic replicons generated from Semliki Forest virus, Sindbis virus, poliovirus, tick-borne encephalitis virus, and others (Ulmer et al, 2012).…”
Section: Comparison Of Dna Vaccine With Rna Vaccine and Recombinant Vmentioning
confidence: 99%